The influence of entrepreneurial-related programmes on student intentions to venture into new business creation - Matsheke, Onica Thandi (Vaal University of Technology, 2015)
Whilst entrepreneurial education has received a fair amount of attention both locally and internationally, there is, surprisingly, still no universally accepted curriculum dedicated to aspiring entrepreneurs at universities which adequately exposes students to an environment that encourages new venture creation. Furthermore, disparities continue to exist in the quality of entrepreneurship education programmes on offer within higher education institutions in South Africa, particularly in curriculum design, delivery methods and forms of assessment. Moreover, an entrepreneurial culture in South Africa has not yet reached the desired national level in comparison to entrepreneurship in other developed nations. This study examines the influence of entrepreneurial-related programmes on students’ intentions to venture into new business creation. This study is located within a quantitative descriptive research paradigm, which permits the testing of relationships among the various constructs through a structured questionnaire. The sample was drawn from final year students of the Faculty of Management Sciences at a university who were studying various business-related programmes in which modules on entrepreneurship were compulsory. Variables included in the study focused on the entrepreneurial content of the curriculum, attitude towards entrepreneurship, intentions towards entrepreneurship and general self-efficacy. Data provided by 263 respondents was analysed using correlation and regression analyses. The results revealed a weak predictive relationship between the entrepreneurial content of the curriculum and the attitude of students to venture into new business creation. In addition, students’ attitudes towards entrepreneurship showed low levels of prediction of students’ intentions towards entrepreneurship. Finally, the results showed that students’ entrepreneurial self-efficacy did not appear to influence their attitude towards entrepreneurship. A possible reason for these results may be the notion that not enough enthusiasm is generated in students because the modules in entrepreneurship, whilst compulsory, are not offered as majors in the curriculum, unlike in dedicated entrepreneurship programmes. The major challenge in entrepreneurship programmes is the appropriateness of the content of the curriculum in developing student’s attitude towards entrepreneurship. Students who are not exposed to the content of the curriculum that allows the commercial use of entrepreneurial knowledge demonstrate a weak attitude towards entrepreneurship. The entrepreneurial content of the curriculum should be enhanced with improved teaching delivery modes that enable students to gain hands-on experience by seeing, touching and ‘feeling’ the business world. Contents of the curriculum should be designed to include learning outcomes which are for entrepreneurship rather than about entrepreneurship. An entrepreneurial content of the curriculum which is developed for entrepreneurship deals with real entrepreneurial activity and produces students who have a positive attitude towards entrepreneurship. In order to enhance the status of entrepreneurship, curriculum developers should include various aspects of entrepreneurship in all years of the students’ study programme. In order for entrepreneurship to be given ‘life’, provision should be made to support incubation start-ups at the university level with practical training. The feasibility of offering a practical, hands-on entrepreneurship programme should be explored.
M. Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Entrepreneurial education; Business studies; New business creation; 658.421; Entrepreneurship -- South Africa.; Dissertations, Academic -- South Africa.